Tobacco consumption and quality of life among teachers: a bidirectional problem - Lizana, Pablo A.; Vilches-Gómez, Valentina; Barra, Lisseth; Lera, Lydia (Frontiers in Public Health, 2024)
Objective: This study aimed to assess a bidirectional relationship between tobacco consumption and quality of life among Chilean teachers.A total sample of 647 Chilean teachers was included in a cross-sectional study (71.8% female). Teachers completed a socio-demographic questionnaire, tobacco consumption habits, and the SF-36 questionnaire to assess quality of life. Logistic regression models were employed for statistical analysis of quality of life (physical component summary; mental component summary), and tobacco consumption habits, adjusted for socio-demographic characteristics.Results: A total of 34.2% of teachers were smokers, with the majority (68.7%) being under 45 years old. Smoking teachers demonstrated lower quality of life scores, particularly mental health and emotional problems dimensions, and mental component summary (p < 0.05) versus nonsmoking teachers. Teachers with tobacco consumption had a higher risk of low mental component summary (OR: 1.74; p < 0.001), and those with low mental component summary were more likely to be smokers (OR: 1.77; p < 0.002).These findings indicate that tobacco consumption adversely affects the quality of life of Chilean teachers, especially their mental health. Psychological support should be provided to help teachers cope with work stress and tobacco consumption.